2022
DOI: 10.1186/s12889-022-13623-w
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to accept COVID-19 vaccination among people living with HIV in a high HIV prevalence community

Abstract: Background People living with HIV (PLWH) may have a poorer prognosis with COVID-19 infection and are an important population for COVID-19 vaccination. We assessed the willingness and reasons for COVID-19 vaccine acceptance or hesitancy among PLWH in South Africa. Methods We conducted a cross-sectional study consisting of telephone interviews with a randomly selected subset of participants enrolled in a prospective observational cohort study evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…South Africa has the highest number of people infected by HIV, which is about 7.9 million or about 13.78 % of the country's population. In addition, about 19.5 % of the infected people are aged 15–49 (Govere‐Hwenje et al, 2022). About 4.9 million of the infected are already in the ARVDs program, thus may increase the volume of ARVDs received by water sources.…”
Section: Introductionmentioning
confidence: 99%
“…South Africa has the highest number of people infected by HIV, which is about 7.9 million or about 13.78 % of the country's population. In addition, about 19.5 % of the infected people are aged 15–49 (Govere‐Hwenje et al, 2022). About 4.9 million of the infected are already in the ARVDs program, thus may increase the volume of ARVDs received by water sources.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Since the start of the pandemic, the proportion of PWH reporting interrupted HIV care, which is associated with worse mortality than consistent engagement in care, has increased. 9 Medical mistrust following the onset of the pandemic has also been documented among PWH in South Africa, 10 possibly contributing to these care interruptions. Pandemic-related increases in poor mental health and substance use and on use of mental health services in South Africa 11 , 12 may also be affecting HIV care engagement.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition, hesitation was found to be associated with medical mistrust, feelings of vaccines being experimental, obtaining information from social media, political conservativeness, and lower education level. [8][9][10][11][12][13] Previous studies among PLHIV have demonstrated safety profiles of various COVID-19 vaccine types including inactivated, 8,14-18 viral vector, [19][20][21] and mRNA vaccines. [21][22][23][24] Overall, most common adverse effects (AEs) of the vaccines were local injection site reactions and systemic reactions including fatigue, fever, myalgia and headache.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Despite the vaccine effectiveness, the rates of COVID-19 vaccine hesitancy among PLHIV ranges from 16%-91% depending on the study settings and the points of time when the studies were conducted. [8][9][10][11][12][13] The main reasons for vaccine hesitation were concerns about safety, 8-13 efficacy [8][9][10][11][12][13] and the impact of the vaccines on antiretroviral therapy (ART) efficacy. 11 In addition, hesitation was found to be associated with medical mistrust, feelings of vaccines being experimental, obtaining information from social media, political conservativeness, and lower education level.…”
Section: Introductionmentioning
confidence: 99%